Vidas do meio fio: os moradores de rua de Fortaleza no contexto da formulação de uma política pública - Lima, Silvana Garcia de Andrade (2008)
In the present work, we have the purpose of discussing the social service politics and its confluence with the segment of street residents who makes the public space their residences and who makes their presence in city one of the expressions of social exclusion. We have proposed ourselves to dialogue, in the Social Service Politics area, with the rising of the public politics intersection of attention to the population in street situation of Fortaleza municipality evaluating the social care ways to the people who lives in street and survives upon it. We have investigated the main facing ways of these groups to survive in the streets, discussing the social circumstances that surround the fact and the effective demands of social care to this segment. In this way the investigative effort happens in a double versant: uncovering the street representations which leads and attracts these groups to the public space and ties them in it, as though as their aspirations to the public power; evaluating the answers that the public politics of social care is building in face to the peculiar reality of street population. This is the challenge to be won in our investigation ride. It is in this perspective that we throw each other in the task of “having eyes of seeing” and going beyond the visible, uncovering this new universe of the “street nomads”, throughout a deeper study of the articulations between the segment of street residents to the nowadays rising politics of care to the street population of Fortaleza